PERBEDAAN KINERJA SAHAM INDONESIA SEBELUM DAN SELAMA MASA PANDEMI COVID-19 - Permana, Arradytia; Nurpiana, Iin; Kosim, Belliwati; Hidayat, Randy (MOTIVASI, 2022)
Purpose – The aim is to find out the difference in the performance of Indonesian stocks before and during the Covid-19 pandemicDesign/methodology –Secondary data is needed as a basis for analysis, while data collection techniques use documentation. The analysis technique used is Paired Sample t Test.Findings - The results of this study indicate that there are differences in the performance of Indonesian stocks before and during the Covid-19 pandemic. The difference is in the downward movement of stock prices.